Seismic Behavior of ¼ Scale Unreinforced Masonry House Models Retrofitted by PP-band Meshes - Sathiparan, N.; Meguro, K. (My University, 2010)
This paper introduces a technically feasible and economically affordable PP-band (polypropylene bands) retrofitting for low earthquake resistant masonry structures in developing countries. Results of the basic material tests and shaking table tests on building models show that the PP-band retrofitting technique can enhance safety of both existing and new masonry buildings even in worst case scenario of earthquake ground motion like JMA 7 seismic intensity. Therefore, proposed method can be one of the optimum solutions for promoting safer building construction in developing countries and can contribute earthquake disaster mitigation in the future.
Keywords: unreinforced masonry; polypropylene bands